A Review of Non-Technical Training Programmes Conducted by Corporate Trainers for IT Companies - Chandni J. Vidani; Nilesh Chaudhary; Vruda Patel (International Journal of Managemen Analytics (IJMA), 2023)
Non-technical skills are increasingly recognized as vital for the success of IT professionals in today's competitive business environment. This qualitative research paper presents a comprehensive review of non-technical training programs conducted by corporate trainers for IT companies. The study aims to explore the types of non-technical training programs offered, their effectiveness, and the perceived impact on employees' skill development and career growth. The paper delves into topics such as leadership development, communication skills, problem-solving, teamwork, and time management. It critically evaluates the content, methodologies, and delivery approaches utilized in these programs, as well as their alignment with the specific needs and challenges faced by IT professionals. This study investigates the perceived effectiveness of these non-technical training programs by exploring their impact on employee performance, job satisfaction, and career progression. It explores the perceptions and experiences of employees who have participated in these programs, using qualitative data collection methods such as interviews, focus groups, and surveys. The analysis delves into the participants' feedback, insights, and recommendations, providing a deeper understanding of the strengths and limitations of the training programs. The findings of this qualitative research offer valuable insights for IT companies, corporate trainers, and human resource professionals involved in designing and implementing non-technical training programs